2017
DOI: 10.1038/srep42875
|View full text |Cite
|
Sign up to set email alerts
|

Altered enhancer transcription underlies Huntington’s disease striatal transcriptional signature

Abstract: Epigenetic and transcriptional alterations are both implicated in Huntington’s disease (HD), a progressive neurodegenerative disease resulting in degeneration of striatal neurons in the brain. However, how impaired epigenetic regulation leads to transcriptional dysregulation in HD is unclear. Here, we investigated enhancer RNAs (eRNAs), a class of long non-coding RNAs transcribed from active enhancers. We found that eRNAs are expressed from many enhancers of mouse striatum and showed that a subset of those eRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Analysing 44 human HD brains, Hodges and coworkers observed a significant decrease in GPR6 expression compared to unaffected controls (Hodges et al 2006). Similarly, in a recent study of striatal transcriptional alterations in HD, the authors detected that the expression of GPR6 eRNA (enhancer RNA) is deregulated in R6/1 HD mouse striatum (Le Gras et al 2017). They further demonstrated that GPR6 expression is reduced in the striatum of R6/1 and Q140 HD mice models.…”
Section: Biological Relevancementioning
confidence: 74%
See 1 more Smart Citation
“…Analysing 44 human HD brains, Hodges and coworkers observed a significant decrease in GPR6 expression compared to unaffected controls (Hodges et al 2006). Similarly, in a recent study of striatal transcriptional alterations in HD, the authors detected that the expression of GPR6 eRNA (enhancer RNA) is deregulated in R6/1 HD mouse striatum (Le Gras et al 2017). They further demonstrated that GPR6 expression is reduced in the striatum of R6/1 and Q140 HD mice models.…”
Section: Biological Relevancementioning
confidence: 74%
“…Two independent research groups provided evidence of the relation between GPR6 and the HD pathology (Hodges et al 2006; Le Gras et al 2017). Analysing 44 human HD brains, Hodges and coworkers observed a significant decrease in GPR6 expression compared to unaffected controls (Hodges et al 2006).…”
Section: Biological Relevancementioning
confidence: 99%
“…Very few studies investigated histone acetylation in pathological context at the genome‐wide level. Our recent studies showed selective decreased H3K27ac at neuronal identity genes regulated by a super‐enhancer, in the striatum of Huntington's disease mice (Achour et al , ; Le Gras et al , ). In the hippocampus of the CK‐p25 AD mouse model, H3K27ac levels were decreased at promoter/enhancers of genes associated with synapse and learning functions and preferentially bound by CBP (Gjoneska et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly evidences implicate that enhancers are functionally important in key cellular processes including cell development, differentiation and apoptosis. eRNAs are generated by the transcription of active enhancers and involve in the development of various diseases by regulating the expression of multiple genes . GREB1 is shown to be one of the most oestrogen‐specific genes and plays an important role in oestrogen‐mediated transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…For the group of eGREB1 knockdown with oestrogen treatment, the cell proliferation was obviously decreased ( Figure 3A, B, P < 0.01 in T24 and 5637); the cell migration ratio were reduced by 11.68% in T24 and 18.28% in 5637 ( Figure 3C-E, P < 0.001 in T24 and 5637); the invasive ability of the cells is also prominently weakened ( Figure 4A-C, P < 0.01 in T24 and 5637); ELISA assay showed that the activity of caspase-3 were increased ( Figure 4E, P = 0.001 in T24, by regulating the expression of multiple genes. [22][23][24][25][26] GREB1 is shown to be one of the most oestrogen-specific genes and plays an important role in oestrogen-mediated transcriptional activation. The corresponding enhancer of GREB1 could transcribe into eGREB1 when exposed to oestrogen.…”
Section: Egreb1 Knockdown Attenuated the Cancer-promoting Effect Ofmentioning
confidence: 99%